KONSELING PERNIKAHAN PERSPEKTIF AL-GHAZALI DALAM KITAB IḤYĀ'U ‘ULŪMI AD-DĪN - Muhammad Hasyim Asy’ari; Wawan Juandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Marriage counseling is a service in helping to solve problems related to marriage. The research method used is the library method. The results of this study indicate that the marriage counseling process according to al-Ghazali includes counseling requirements and counseling steps. Fulfillment of counseling requirements include the purpose of marriage counseling, effective counselor and counselee criteria, the relationship situation includes the situation between parents and children; between teacher and student; between friends and between families. The counseling steps are building relationships, identifying problems, determining material and actions. The counseling material is the purpose of marriage, motivation and prevention of marriage, the principle and danger of marriage, criteria for a good partner, adab reception, having good character and patience in facing suffering, joking and laughing, stability according to the partner's wishes, stable in jealousy, simple in spending , teach religion, act fairly, adab settlement, disputes, marital conduct, labor, divorce and the rights and obligations of husband and wife